Implementasi Program Budaya Sekolah (School Culture) di SMP IT Daarul Muttaqien - Zahara Mustika (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Implementing school culture is crucial to creating a positive and effective learning environment. SMP IT Daarul Muttaqien is known to have a school culture program. However, no further research has been conducted on how the school culture program is implemented at SMP IT Daarul Muttaqien. This study aims to determine the strategy for implementing school culture and its principles in developing it. The research method used is descriptive qualitative. Because it wants to describe the implementation of the school culture program based on interviews with the school (principal, committee, and teachers), observations, and school documentation. The principal, committee, and teachers were selected as sources to obtain information related to the implementation of the school culture program as it has been carried out at the school. Observations were made to observe how the school culture program is run by the school. Documentation was carried out to visualize the objects of the school being studied. Information data was analyzed using the Miles method and triangulation. The results of the study showed that the strategy for implementing school culture was carried out by involving all stakeholders in the school. The implementation of school culture in principle has been implemented by the school which took place in stages, namely the development of school culture, innovation, performance, evaluation, involvement in decisions, and reward systems.